Effect of COVID-19 lockdown on the livelihood of street vendors in Maharashtra, India - Meher, Sonu R.; Ranjan, Alok; Shukla, Parul; Atram, Yogita (International Journal Of Community Medicine And Public Health, 2021)
Background: As the COVID-19 pandemic unfolded, the lockdown was implemented as the main preventive measure to contain the spread of the virus across the world. India also went under one of the most stringent nationwide lockdowns which affected the workers of the informal sector the most. This study aims to explore the impact of the COVID-19 and lockdown on the livelihood of street vendors in the Maharashtra state, one of the severely affected states, of India. Methods: Telephonic in-depth interviews were conducted from 16th May to 1st June 2020 with 20 street vendors who sold perishable goods for their livelihood. Interviews were transcribed and thematic analysis was used in analysing the data. Results: There were a total of twelve food vendors and eight fruits and vegetable vendors in the study sample. The mean age of food vendors recorded was 36.91 years; the average years of working recorded were 12.25; the mean education level was 7.83; and the average household size recorded was 5.25. Out of the total food vendors, 10 were males and two were females. The majority of the food vendors belong to the Vidarbha region, followed by Khandesh and Western Maharashtra. Conclusions: Findings of the study show that lockdown affected street vendors multidimensionally. Street vendors had to stop working and many had to change their profession to selling fruits and vegetables within a limited time zone with greater livelihood challenges and financial hardships.